International social security law - Servais, Jean-Michel (Kluwer Law International, 2020)
Although a sophisticated body of international social security law is active and growing, a number of States still appear unable to honour it. This thorough, well-researched survey and analysis of existing international social security - its sources, its content, its historical development - is thus especially valuable for its informed consideration of the barriers to the law's full effectiveness. Part of the renowned multi-volume Encyclopaedia of Laws, the book focuses on the analysis of the International Labour Organization (ILO) Conventions and Recommendations on Social Security. It examines the most recent public debates on social protection (dealing with health insurance, unemployment benefits, pension age, minimum income, social security benefits in case of expatriation, parental leave, and much more), includes an updated bibliography, and opens some perspectives for the future work of the global institutions. It integrates the latest instruments, in particular ILO Recommendation No. 202 concerning national floors of social protection. Even in the absence of ratification and therefore of legal force, international social security standards are invaluable benchmarks in comparative law. Indeed, ILO standards are both useful instruments of analysis and excellent yardsticks for identifying common denominators among national systems. For these reasons this book will be welcomed by legislators, government officials, employers'organizations, trade unions, and the judiciary, as well as by human resources managers and academics.